Analisis Sensori dan Kadar Polifenol Minuman Fungsional Teh Bunga Telang (Clitoria ternatea L) dan Kurma (Phoenix dactylifera L) : Sensory analysis and polyphenol content of functional drinks of butterfly pea flower tea (Clitoria ternatea L) and date palm (Phoenix dactylifera L) - Anwar, Khoirul; Khoirunnisaa , Tasya (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2024)
Functional drinks are drinks that contain elements of nutrients or non-nutrients and can have a positive effect on the health of the body. Polyphenols are a component of functional drinks that have physiological functions for the body. This study aims to determine the levels of polyphenols in tea from butterfly pea flower and date palm. The design used in this study was a completely randomized design with one factor and five levels of three replications. The treatment factor was the ratio of butterfly pea flower tea and date palm extract 70:30, 60:40, 50:50, 40:60 and 30:70 (v/v). The materials used for the manufacture of the product are butterfly pea flowers, dates and water. Tests carried out on tea from butterfly pea flower and date palm products were color intensity test, pH test, total polyphenol test and sensory analysis. The study used the ANOVA statistical test with a significance of ρ=0.05. The results of the polyphenol content test showed that the tea from butterfly pea flower and date palm formulation with a ratio of 40:60 had the highest polyphenol content with a value of 375.7 mg/kg. The formulation of the tea from butterfly pea flower and date palm with a ratio of 70:30 is the best formula with an L* value of 5.178, a* value -1.688, b* value of 1.185, pH value of 7.47, polyphenol content of 203.7 mg/kg, deep bluish green color, strong butterfly pea flower aroma, and a slightly sweet taste. The formulation of tea from butterfly pea flower and date palm with a ratio of 40:60 has the highest levels of polyphenols and has a deep bluish green color, strong butterfly pea aroma, and a slightly sweet taste.